Paternalistic Leadership in Kuwaiti Business Environment: Culturally Endorsed, but Largely Ineffective - Adžić, Slobodan; Almutairi, Shihanah (Industrija, 2021)
There is an assumption from the reviewed literature that Paternalistic Leadership (PL) is culturally endorsed as a leadership style in Kuwait. With many diverse perspectives on the effectiveness of paternalistic leadership, the research objectives of the current research are threefold. First, to examine if PL is recognized as a leadership style in Kuwait organizations, second, to test the effectiveness of that style if present, and third, to identify the specifics of the Kuwaiti leadership practice. The findings lead to the conclusion that PL is present in Kuwaiti leadership practices, culturally is endorsed, but otherwise is considered as an ineffective leadership style because of the influence of wasta.
Keywords: Paternalistic Leadership, Kuwait, Culture, Leadership, Wasta.